Mechanical Characterization of hiPSC‐Derived Cardiac Tissues for Quality Control. Issue 12 (24th October 2018) - Park, Seungman; Lui, Cecillia; Jung, Wei‐Hung; Maity, Debonil; Ong, Chin Siang; Bush, Joshua; Maruthamuthu, Venkat; Hibino, Narutoshi; Chen, Yun
Abstract: Heart disease is one of the leading death causes in developed countries. To facilitate heart rehabilitation, engineered cardiac implantation has emerged as a promising alternative to organ transplantation. Currently there is no quantitative standard to ensure the safety and functionality of the engineered cardiac tissues intended for clinical uses. In anticipation of the clinical application of the engineered cardiac tissues to heart disease patients, a suite of methods is assembled to evaluate the mechanical characteristics critical to cardiac functions, including contractility, viscoelasticity, and dynamic stress distribution. As a proof of concept, 3D bioprinted cardiac tissues derived from human induced pluripotent stem cells are tested. First, the engineered cardiac tissues labeled with particles are recorded and tracked to determine spatially and temporally variable contraction forces. Viscoelastic properties are measured using magnetic tweezers. The results are used to compute 3D force and stress distribution over the engineered tissue by finite element method. In summary, a framework is developed to assess clinical‐grade engineered cardiac tissues and determine the appropriate value ranges suitable for implantation. The results relating contractility, intrinsic mechanical properties, and stress distribution in the engineered tissue, can also inform better design for future fabrication of engineered tissues. Abstract : In anticipation of the clinical application of engineered cardiac tissues, a suite of methods combining fluid mechanics, live imaging, and magnetic tweezers is developed to measure the properties critical to cardiac function, including beating frequency, contractile forces, and tissue viscoelasticity. The measured mechanical properties are integrated to compute 3D stresses experienced dynamically by engineered tissue.